From Pikulan to Culinary Center: The Historical Transformation of Lentog Tanjung in Kudus, 1952–2014 - Wardati, Mutiara; Bashori, Muzakki (Universitas Hamzanwadi, 2026)
Traditional cuisine is an important part of cultural heritage that reflects the social, economic, and identity dynamics of a community. This study examines the history and development of Lentog Tanjung as a traditional culinary specialty of Kudus from 1952 to 2014, as well as its transformation from a common people’s food sold using shoulder poles (pikulan) into a culinary center. This research employs a qualitative approach using the historical method through the stages of heuristics, verification, interpretation, and historiography. Data were obtained from literature studies, documentation, and interviews with business actors, local communities, village officials, and the Department of Culture and Tourism (Disbudpar) of Kudus Regency. The results show that Lentog Tanjung functions not only as a culinary dish commonly consumed for breakfast by people in Kudus and outside the region, but also as a representation of cultural identity that has developed alongside social and economic changes. The shift in the selling system from mobile shoulder-pole vendors to permanent stalls in a culinary center has strengthened its position as a regional culinary icon while also encouraging local economic growth. This transformation has also influenced changes in gender roles, marked by the increasing participation of women in the production and sale of Lentog Tanjung. The sustainability of this culinary tradition is supported by the consistency of its authentic taste and presentation, as well as support from the community and local government in organizing the area and preserving traditional cuisine.